BANJAR WIJAYA LIBRARY CONCRETE PANEL WALL - Widodo Kushartomo; Ariiq Ananta Lukman; Ahmad Septian Dewanto; Ester Stella Luwih Budi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2022)
The wall is one of the building elements that serve to separate/form a space. In the construction of the Banjar Wijaya library, Cipete Village, Pinang District, Tangerang City, all the walls use thin and patterned concrete panels. The use of thin concrete walls is intended to make strong and durable semi-permanent buildings. Strong in this case the wall is not easily broken or perforated and durable which means resistant to weather attacks and termites. The building frame is made of galvanized hollow iron, with bolt and weld connection methods to ensure the strength of the building. The concrete panels are installed on the inner wall with a thickness of 6 mm, the ceiling with a thickness of 4 mm, the floor with a thickness of 20 mm, the outer wall with a thickness of 4 mm. All installation is done using bolts for time and cost savings. On the outer wall, the concrete panels are lined with wood-patterned concrete panels with a thickness of 6 mm to enhance the appearance of the library building. The library building is a collaboration between residents of RW 07, Cipete Village, Banjar Wijaya, Tangerang City, and the Tarumanagara University PKM team from the Civil Engineering Undergraduate Study Program.